Promoting emotional & behavioral health for pediatric patients with Fontan circulation: integrating psychology into a dedicated multidisciplinary clinic - Seivert, Nicholas P.; Dodds, Kathryn M.; Demianczyk, Abigail; Goldberg, David J.; Rychik, Jack (Frontiers in Cardiovascular Medicine, 2025)
IntroductionIndividuals with single ventricle congenital heart disease and Fontan circulation are at high risk for mental health problems. There is a lack of information about potential care models to address these common challenges. This study describes the innovative integration of psychology consultations into a multidisciplinary clinic for pediatric patients with Fontan circulation. Findings from emotional/behavioral and quality-of-life measures are reported and relationships between these variables are explored.MethodThe Fontan Rehabilitation, Wellness and Resilience Development (FORWARD) Program at Children's Hospital of Philadelphia is a multidisciplinary clinic for individuals with Fontan circulation. A psychologist provides behavioral health consultations to all clinic patients. The psychologist engages in real-time care coordination and treatment planning with the multidisciplinary team. Families are administered standardized screening questionnaires assessing child emotional/behavioral functioning (Behavior Assessment System for Children-3) and quality-of-life (Pediatric Cardiac Quality of Life Inventory). The psychologist provides brief behavioral intervention and recommendations for follow up care. Patient data were gathered by chart review. Correlations explored the relations between selected screening measures.Results158 patients (mean age = 12.5 years) were seen between January 2019 – June 2022. 92% completed a psychology consultation. Most had hypoplastic left heart syndrome (54%), were male, White, and had commercial insurance. A majority completed at least one of the screening measures. Elevated symptoms were found for 23% of the sample for depression/anxiety, 37% for inattention, and 22% reported school problems. Findings from the quality-of-life measure showed mild to moderate impairment for the sample. Greater inattention, depression/anxiety, and school problems correlated with lower quality-of-life scores.DiscussionThis study demonstrates the feasibility of innovatively implementing regular psychology consultations into a multidisciplinary clinic for children and adolescents with Fontan circulation. Greater emotional/behavioral problems were associated with poorer quality-of-life. Fully integrated care models that include including behavioral screening measures are optimal to address emotional/behavioral challenges in this population. Less resource intensive models could be implemented as pilot programs to establish feasibility and utility. Research is needed to evaluate efficacy of such programs and examine potential links between medical and psychological variables.